Reverse translation in the dubbing of cultural elements: a didactic proposal with emphasis on the professional workflow - Ogea Pozo, Mª del Mar; Botella Tejera, Carla (Estudios de Traducción, 2023)
This paper studies the perception and preferences of translation regarding cultural elements by Spanish-speaking students, being viewers and translators, in the dubbing of the series Valeria (Torrente y Reguera 2020), so as to examine the solutions provided by Netflix. Through the comparative analysis of the results, our aim is to improve the professional practice of audiovisual translation into English. This contribution may be useful for Spanish-speaking translators, who usually transcribe Spanish productions and create templates in the source language, as well as a first version in English, which is then revised by an English-speaking translator. The results reveal the extent of coincidence in the perception and translation techniques chosen by the agents involved in the process, who are responsible for ensuring that the cultural elements are conveyed successfully.
Keywords: audiovisual translation; reverse translation; training; dubbing; cultural elements